Patient Delay in Initiating Tuberculosis Treatment and Associated Factors in Oromia Special Zone, Amhara Region - Abdu, Muhammed; Balchut, Awraris; Girma, Eshetu; Mebratu, Wondwosen (Pulmonary Medicine, 2020)
Background. Tuberculosis (TB) is a major global public health problem. The disease is a leading cause of morbidity and mortality in Ethiopia. Early identification of cases and commencement of effective chemotherapy is an effective method to control the spread of tuberculosis. Delay in diagnosis and starting tuberculosis treatment increases severity, risk of mortality, and transmission of the disease in the community. Objective. The purpose of this study is to assess the magnitude of patient delay in initiating tuberculosis treatment and its associated factors among tuberculosis patients in health facilities of Oromia Special Zone, Ethiopia. Methods. A facility-based cross-sectional study was conducted in Oromia Special Zone. Data were collected using pretested questionnaires from patients with tuberculosis who are on treatment during the study period. The simple random sampling method was used to select health facilities and study participants. Data were entered using Epi Info version 7.2 and analyzed by SPSS version 23. Bivariate and multivariate logistic regression analyses were used to see the significance of association between the outcome and independent variables. A P value < 0.05 was considered statistically significant. Results. Three hundred and eighty-seven tuberculosis patients aged 18 years and above enrolled in the study. Among these, 223 (57.6%) were males, 194 (50.1%) were married, and 206 (53.2%) lived in rural areas. The mean age of respondents was 35 years. The median patient delay was 35 (IQR=30) days, and 54.4% of patients seek their first consultation after 21 days. Patients who have a basic schooling level (AOR=0.45, 95% CI: 0.23, 0.89) compared with the college/university level, long distance greater than 10 km (AOR=3.23, 95% CI: 1.97, 5.42), seeking treatment from informal source and private drug stores (AOR=3.01, 95% CI: 1.52, 5.95), extrapulmonary tuberculosis (AOR=2.30, 95% CI: 1.26, 4.23), and poor knowledge about tuberculosis (AOR=1.58, 95% CI: 1.01, 2.49) were associated factors that predict patient delay. Conclusion and Recommendation. A significant proportion of tuberculosis patients delayed to seek treatment. Health promotion and education involving different stake holders will make the community create awareness about tuberculosis that could help reduce delays in initiating tuberculosis treatment.